Thyroid-stimulating antibody activity between different immunoglobulin G subclasses. - Weetman, A P (1990)
To investigate the distribution of thyroid-stimulating antibody (TSAb) activity between IgG subclasses, sera from 11 patients with Graves disease (including the National Institute of Biological Standards and Control (NIBSC) Research Standard, long acting thyroid stimulator-B) were fractionated by chromatography on affinity columns of monoclonal IgG subclass antibodies or protein A to deplete all but a single subclass. The resulting fractions were 98% or more pure for a single subclass. In all 11 patients, TSAb activity appeared to be confined to the IgG1 fraction as determined by cAMP production on addition of the fractions to the FRTL-5 rat thyroid cell line. In all of eight specimens from seven patients so tested, the whole serum activity was recovered in the IgG1 fraction, after adjusting for the recovery of the isotype from the column. TSAb activity in one serum comprised both lambda and kappa light chains but was IgG1 restricted. This IgG subclass restriction was not found when the same fractions were tested for thyroglobulin, microsomal/thyroid peroxidase, or tetanus toxoid antibody activity. Together with previous results showing marked restriction of both light chain usage and isoelectric point of TSAb, these results support the idea that Graves' disease may be the result of an oligo- or possibly monoclonal response at the B cell level.